The intuitionist - Whitehead, Colson (London : Fleet, 2017)
An elevator inspector becomes the center of controversy when an elevator crashes. The inspector, Lila Mae Watson, is a black woman who inspects by intuition, as opposed to visual observation, and now she must prove her method was not at fault. A study of society's attitude to technology and a debut in fiction.
Originally published: New York : Anchor Books, 1999.
Roman
Science fiction
ENH
Karim International
Keywords: Whitehead, Colson -- 1969-; Elevators Inspection -- Fiction; English literature; African American women -- Fiction; African Americans -- Fiction